Mechanical and thermal characterization of hybridized short kenaf/pineapple leaf fiber reinforced high density polyethylene composites - Isuwa, Suleiman Aji (2011)
Hybrid composites of kenaf/pineapple leaf fiber (PALF) reinforced highdensity polyethylene (HDPE) matrix were produced by compression molding operation. Tensile, impact and flexural tests as well as dynamic mechanical and thermogravimetric analyses (DMA and TGA) were performed to characterize the composites in variation to fiber loading, fiber length and kenaf/PALF fiber proportions. This is in addition to employing electron beam irradiation (EBI), use of compatibilizers/modifiers and crosslinkers in improving the composites mechanical properties. Characterisation of the composites was preceded with the optimization of the composite‘s processing parameters. Hybridization has shown to provide better impact strength and reduction in overall water uptake of composites even without carrying out any chemical treatment. While PALF has improved the composite in tensile and flexural properties, kenaf provided impact strength and reduction in the overall water uptake because of its better aspect ratio that ensured greater matrix dispersion in the composites. Furthermore, tensile and flexural properties of the hybrid are higher than that of the neat HDPE and this increase is in direct proportionality to increase in fiber loading for up to an optimum of 60% with 0.25mm fiber length; however, the impact strength of all un-modified hybrids was lower than that of neat HDPE except where EBI was employed at 10 kGy. Increasing fiber length did not show proportionate improvement in tensile and flexural properties, which could have been caused by fiber agglomeration, but impact strength showed otherwise. Treatment of fiber surface with NaOH and Vinyltri(2-methoxy ethoxy) silane (silane AH172) and modification of HDPE matrix with the addition of MaPE and Poly (methylene) poly(phenil) isocyanate (PMPPIC) for the purpose of curtailing water uptake of the composite was successful. Irrespective of either fiber surface modification or matrix modification, reinforcement with respect to treatment depends on the type of modifier used and not the modification of matrix or fiber. Composites responded marginally to trimethylol propane trimethacrylate (TMPTMA) and silane that were employed as crosslinkers because HDPE self-crosslinked by radiation making silane and TMPTMA less effective, thus, radiating such composite without their addition is preferred. Thermal property from DMA results has shown that at lower temperatures,60% fiber loading had reduced the loss modulus peak of the neat HDPE and delayed the loss modulus of the hybrid up to about 100 oC. However,increasing the fiber content of the hybrid composite, raised the damping peak (tan delta) with increase in temperature. Thermogravimetric analysis (TG) and derivative thermogravimetric analysis (DTG) result showed that the main decomposition temperature occurred around 467 oC for all except composites prepared with 0.75 and 2 mm fiber length. There was a clear shift in decomposition temperatures of the composites with increase in fiber length while decomposition of hybrid composite is directly proportional to increase in fiber loading. In conclusion, kenaf and PALF offered tremendous potential as hybrid fillers in HDPE matrix. They have shown to enhance thermal stability of composites,ease higher fiber loading vis-à-vis improved mechanical properties of matrix and reduction in water uptake even without treatment/ compatibilization. This combination holds the edge for practical engineering application in automobile dashboard, side driving mirror casing and automobile door trim fabrication.